Alpha-ketoglutarate rescues impaired endothelial progenitor cell-mediated angiogenesis in diabetic mice - Qiu, Jing-Hui; Ruan, Xiao-Bao; Jiang, Yu; Shi, Wen-Ting; Tao, Xia; Chen, Alex F.; Peng, Cheng; Xie, He-Hui (Frontiers in Pharmacology, 2025)
It is of great clinical significance to develop potential novel strategies to prevent diabetic cardiovascular complications. Endothelial progenitor cells (EPCs) dysfunction plays a critical role in the development of diabetic vascular complications. In the present study, we evaluated whether alpha-ketoglutarate (AKG) could improve the impaired function of EPCs, rescue EPC-mediated angiogenesis, and prevent cerebral ischemic injury in diabetic mice (Mus musculus). Diabetes was induced in mice by five consecutive injections of streptozotocin (STZ, 60 mg·kg−1·d−1, i. p.). The diabetic mice were randomly divided into two groups, half of the mice were treated daily by oral gavage with AKG (4 g·kg−1·d−1), and the other half were treated daily with the same amount of vehicle (saline solution) via gavage for 4 consecutive weeks. We found that administration of AKG significantly reduced the cerebral ischemic injury, promoted angiogenesis and improved EPCs function in diabetic mice. In mice just after middle cerebral artery occlusion, intravenous injection of AKG-treated diabetic EPCs displayed a greater ability to promote local angiogenesis and reduce cerebral ischemic injury compared to injection of diabetic EPCs treated with vehicle. Furthermore, we found that AKG significantly increased the expression of manganese superoxide dismutase (MnSOD) and copper-zinc SOD (CuZnSOD), decreased intracellular O2·- levels, and attenuated inflammation in EPCs of diabetic mice. In cultured human umbilical vein endothelial cells (Homo sapiens, HUVECs), AKG (0.5 mM) rescued the functions of high glucose-stimulated HUVECs by reducing inflammation through the toll-like receptor 4 (TLR4)/nuclear factor kB (NF-κB) pathway and attenuating oxidative stress. In conclusion, AKG can enhance EPCs’ angiogenic potential and protect against cerebral ischemic injury in diabetic mice. It is implied that chronic treatment with AKG may be a safe and promising option to prevent ischemic diseases (including stroke) in diabetes.